2022
DOI: 10.3390/w14030289
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regional Spatiotemporal Variations in Drought from the Perspective of Soil Moisture in Guangxi, China

Abstract: Understanding the changes in regional droughts is important for promoting overall sustainable development. However, the spatiotemporal dynamics of soil droughts in Guangxi under the background of global warming and regional vegetation restoration have not been studied extensively, and the potential causes are scarcely understood. Here, using TerraClimate soil moisture data, we constructed a monthly standardized soil moisture index (SSMI), analyzed the seasonal and annual spatiotemporal distribution of droughts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In terms of the sugarcane growth stages, the stem elongation stage was found to be the period during which sugarcane drought and flood were most intensive in a year. A similar finding was observed in another study on soil droughts in Guangxi [44]; that report indicated that soil droughts occurred frequently during autumn and winter seasons in Guangxi, which mainly corresponded to the stem elongation stage. However, when the influences of growth stage length were considered, the mature stage had the greatest probability of drought and flood occurrence per month; by contrast, the tillering stage had the minimum probability, which has been reported in a relevant study that focused on sugarcane drought in Guangxi [25].…”
Section: Spatial-temporal Characteristics Of Sugarcane Drought and Fl...supporting
confidence: 89%
“…In terms of the sugarcane growth stages, the stem elongation stage was found to be the period during which sugarcane drought and flood were most intensive in a year. A similar finding was observed in another study on soil droughts in Guangxi [44]; that report indicated that soil droughts occurred frequently during autumn and winter seasons in Guangxi, which mainly corresponded to the stem elongation stage. However, when the influences of growth stage length were considered, the mature stage had the greatest probability of drought and flood occurrence per month; by contrast, the tillering stage had the minimum probability, which has been reported in a relevant study that focused on sugarcane drought in Guangxi [25].…”
Section: Spatial-temporal Characteristics Of Sugarcane Drought and Fl...supporting
confidence: 89%
“…The SMI is defined as the percentage of actual soil moisture in the field capacity, reflecting the relative dryness of the soil. The SMI can be used to detect droughts in specific soil types in small-scale areas, but it has limitations [65]. Although the VSWI monitoring method is intuitive, it is easily affected by cloud and vegetation conditions.…”
Section: Ssmi-based Identification Of Drought Eventsmentioning
confidence: 99%